Atmospheric pressure chemical ionization mass spectrometry of retro‐carotenoids. (31st January 2022) - Schex, Roland; Schweiggert, Ralf; Steingass, Christof B.
Abstract : Rationale: The single and double bonds of the polyene chain of the studied retro ‐carotenoids are located at the neighboring positions compared to those of regular carotenoids. Our mass spectrometry approach targeted at facilitating the characterization of retro ‐carotenoids as their structural diversity in nature is not yet fully elucidated. Moreover, extended π‐electron systems endow several retro ‐carotenoids with exceptional colors from golden‐orange to vibrant red that stimulate the food industry's interest. Methods: Atmospheric pressure chemical ionization‐quadrupole time‐of‐flight‐high‐resolution mass spectrometry (APCI‐QTOF‐HRMS) experiments of the three structurally related retro ‐carotenoids rhodoxanthin, eschscholtzxanthone, and eschscholtzxanthin were performed to elucidate the formation of specific ion species compared to those of the common carotenoids lutein and zeaxanthin. Mass fragmentations of the aforementioned retro ‐carotenoids were unraveled using APCI‐tandem mass spectrometry (MS/MS) in the negative and positive ion modes. Results: Abundant in‐source fragment ions [M + H − H2 O] + of eschscholtzxanthin and eschscholtzxanthone were formed in the positive ion mode owing to the loss of water at the hydroxylated ε‐rings. Eliminations of the ε‐rings at the characteristic exocyclic double bonds at C‐6, 7 and C‐6′, 7′ were observed after the resonance‐stabilized loss of water. Distinct product ions were yielded for all retro ‐carotenoids assessed because of the cleavage at their typical central single bond at C‐15, 15′. Conclusions: Detailed APCI‐QTOF‐HRMS analyses enabled a highly accurate detection of the most abundant ion species and respective signal intensity ratios of retro ‐carotenoids, facilitating their further screening and reliable identification in natural sources. Mass fragmentations of the studied retro ‐carotenoids were found to be substantially impacted by the extraordinary configuration of their polyene backbone.